THE PRINCIPALâS SUSTAINABLE LEADERSHIP AND THE RELATION WITH TEACHERSâ ORGANIZATION COMMITMENT: A CASE STUDY OF GOVERNMENT ASSISTANCE RELIGIOUS SCHOOL - Md Hussian, Shabita; Norhaini Mansor, Azlin (Proceeding 7th International Seminar on Regional Education, 2015)
Abstrak Efficiency and effectiveness of school is related to and affected by the practice of principalâs leadership in an organization. The leadership practice is fundamental to an organization governed pattern. Features found in a leader in this regard will affect the course of an organization in achieving its own goals. The effective practice of leadership often times contribute to a high level of commitment to work or vice versa. In parallel, descriptive research survey was conducted to identify the principalâs sustainable leadership practices and the correlation of the level of organizational commitment among teachers in government-aided religious schools (SABK) in Selangor. This research involves a school government funded religious secondary in Klang area, SAM Nurul Iman. Respondentsâ population for this study consistedall teachers of SAM NurulIman total of 48 people. Data were analyzed using the StatisticalPackagefor SocialScience (SPSS) software version 22.0 to get the mean score, standard deviation and Pearson correlation. Data were collected using a questionnaire developed and modified by the Sustainable Leadership Theory founded by Hargreaves and Finn (2006) and Theory of commitment by Allen and Meyer (1991).Keywords: practice sustainable leadership, organizational commitment, principals, SABK